DESCRIPTION OF THE LEVEL OF PATIENT SATISFACTION WITH NURSING SERVICES IN PATIENT DR. DRAJAT PRAWIRANEGARA SERANG - Lusiani, Milawati; Yusnita, Erny; Rachmaniah, Dini; Mujiyanti , Sri; Nurhayati; Puspa Sari, Ike (AGUSPATI Research Institute, 2020)
Prime nursing services are services provided to patients based on quality standard to meet the needs and wants of patients so that patients can get satisfaction (Qingwei, 2012) The purpose of this research is to know the description of Patient Satisfaction Level on Nursing Service in Inpatient Room of RSUD dr. Drajat Prawiranegara Serang 2018. Variables in this study are attitude, action, attention, responsibility, ability, appearance. The research method used is descriptive with the number of samples 92. Sampling technique used is a quota sampling technique. The results of each variable were satisfied with attitude result (80,4%), action (57,6%), attention (48,9%), responsibility (79,3%), ability (75,0% ), and appearance (65.2%). Suggestion from researcher expected RSUD dr. Drajat Prawiranegara can improve the reliability and quality of nursing services in order to achieve excellent service for patients.